STRENGTHENING THE MEANING OF PERSUASIVE CONTEXT OF BAWASLU PUBLIC SERVICE ADVERTISEMENTS THROUGH ADVERTISING LANGUAGE STRATEGIES: MENGUATKAN MAKNA KONTEKS PERSUASIF IKLAN LAYANAN MASYARAKAT BAWASLU MELALUI STRATEGI BAHASA PERIKLANAN - Rizqi Puspawati; Dewi Kusumaningsih; Sri Muryati (LLDIKTI Wilayah X, 2024)
Bawaslu is an election monitoring agency. In conveying important messages about the election process to the community, Bawaslu uses public service advertisements. Advertising language strategies are needed to strengthen the attractiveness, clarity and persuasive impact of messages conveyed by Bawaslu. This article identifies using advertising language strategies to increase Bawaslu's persuasive messages on the official Bawaslu RI YouTube account. This research aims to provide an in-depth understanding of the use of various forms of language in Bawaslu's public service advertising strategies and to explain how the choice of advertising language strategies can strengthen persuasive messages. This research uses a descriptive qualitative method with data from two videos uploaded by Bawaslu RI and then transcribed in written form. The research results show that Bawaslu utilizes three language strategies to strengthen persuasive messages in public service advertisements, namely (1) choosing diction or word choices that tend to be persuasive, (2) using language analogies or conceptual comparisons, and (3) strengthening the meaning of the message through illustrations or images that are relevant to the context. This research can provide input for Bawaslu and similar institutions in designing more effective public service advertisements in the future.